The Eurasian State of Georgia in the Fourteenth Century : the Mongol Era and Its End. - Kiknadze, Vazha (The Edwin Mellen Press, 2012)
The first and only detailed study of Fourteenth Century Eurasia, an often neglected period in history.
Keywords: Mongols -- Georgia (Republic) -- History -- To 1500.; Georgia (Republic) -- History -- To 1801 -- Sources.; Mongols -- Géorgie (République) -- Histoire -- Jusqu'à 1500.; Géorgie (République) -- Histoire -- Jusqu'à 1801 -- Sources.; HISTORY -- Europe -- Eastern.; HISTORY -- Europe -- Former Soviet Republics.; HISTORY -- Europe -- Russia & the Former Soviet Union.; Mongols; Georgia (Republic); To 1801; History; Sources